1,8-DIAZAFLUOREN-9-ONE (DFO) : A METHOD FOR LATENT FINGERMARKS DETECTION (Journal of Forensic Medicine & Toxicology, 2019)
1,8-diazafluoren-9-one (DFO) is a chemical method for the detection of latent fingermarks on dry, porous surfaces such as paper, cardboard, wood etc. It is an amino acid sensitive reagent. The method is based on interaction of DFO with amino acid fraction of latent fingermarks. The method develops clear, stable, pale pink colored fingerprints which are fluorescent in nature. It is an efficient, non-destructive and rapid procedure for developing latent fingermarks.
Keywords: Latent fingermarks; Amino acids; 1,8- diazafluoren-9-one; Fluorescence; Porous Surfaces